2019
DOI: 10.1002/jmri.26674
|View full text |Cite
|
Sign up to set email alerts
|

Transition zone prostate cancer: Logistic regression and machine‐learning models of quantitative ADC, shape and texture features are highly accurate for diagnosis

Abstract: Background The limitation of diagnosis of transition zone (TZ) prostate cancer (PCa) using subjective assessment of multiparametric (mp) MRI with PI‐RADS v2 is related to overlapping features between cancers and stromal benign prostatic hyperplasia (BPH) nodules, particularly in small lesions. Purpose To evaluate modeling of quantitative apparent diffusion coefficient (ADC), texture, and shape features using logistic regression (LR) and support vector machine (SVM) models for the diagnosis of transition zone P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
0
28
1
1
Order By: Relevance
“…Of those, PCa was found in one fourth after mpMRI fusion biopsy of the prostate. Although this rate seems rather low, it should be taken into account that more than one third of the patients scheduled for HoLEP presented with a history of one or more negative biopsies (8)(9)(10). In contrast to our findings, Preisser et al observed a detection rate of 71.6% in biopsy naïve, 50.9% in patients after one negative biopsy, and 43.5% after two negative biopsies for mpMRI fusion biopsy (11).…”
Section: Discussioncontrasting
confidence: 99%
“…Of those, PCa was found in one fourth after mpMRI fusion biopsy of the prostate. Although this rate seems rather low, it should be taken into account that more than one third of the patients scheduled for HoLEP presented with a history of one or more negative biopsies (8)(9)(10). In contrast to our findings, Preisser et al observed a detection rate of 71.6% in biopsy naïve, 50.9% in patients after one negative biopsy, and 43.5% after two negative biopsies for mpMRI fusion biopsy (11).…”
Section: Discussioncontrasting
confidence: 99%
“…Another useful application of ML MRI has been reported for the accurate distinction of stromal benign prostatic hyperplasia from PCa in the transition zone, a challenging diagnosis particularly in the presence of small lesions. Using ML based statistical analysis of quantitative features such as ADC maps, shape, and image texture, immense diagnostic accuracy in the of differentiation between small neoplastic lesions from benign ones was demonstrated [ 202 ].…”
Section: Selected Examples On Mri Biomarkers In Solid Tumorsmentioning
confidence: 99%
“…Database and model construction are a breakthrough point of radiomics analysis that could be applied as a powerful assistant tool for diagnosis and treatment effect prediction. After that, the classifier or prediction model is usually built with machine learning algorithms, which mainly known as Support Vector Machine (SVM) [47,48], Logistic Regression [49], Random Forest (RF), Decision Tree (DT), clustering analysis, etc. Besides, Convolutional Neural Network (CNN), Artificial Neural Network (ANN), K-Nearest Neighbor (KNN), Holistically Nested Network (HNN) [50,51], etc., which belong to rapiddeveloping deep learning, really accelerated the pace of radiomics progress.…”
Section: Feature Selection and Construction Of Clinical Prediction Momentioning
confidence: 99%